Arte y Estado en la España contemporánea: los orígenes del Museo Nacional Centro de Arte Reina Sofía (1979-1988) - Ait Moreno, Isaac (Anales de Historia del Arte, 2010)
We study on this paper the origins of the Museo Nacional Centro de Arte Reina Sofia (MNCARS), as an example of the particular methodology required to research on art museums history, given that it implies artistic, political and cultural issues. As we try to prove, the specific situation of post-Franco Spain is decisive on the creation of the MNCARS project. If the first plans of the Ministry of Culture with regard to the building of the former Hospital General of Madrid were to fill it with pre-existing institutions, a range of political and cultural factors will determine the birth of a new national museum of modern and contemporary art, which starts a new era on Spanish heritage politics.
Keywords: Museo Nacional Centro de Arte Reina Sofia; Spanish cultural policy; Spanish Ministry of Culture; Carmen Gimenez; Tomas Llorens; Maria de Corral